Airfoil friction drag reduction based on grid-type and super-dense array plasma actuators - FANG, Ziqi; ZONG, Haohua; WU, Yun; LIANG, Hua; SU, Zhi (Plasma science & technology, 2024)
To improve the cruise flight performance of aircraft, two new configurations of plasma actuators (grid-type and super-dense array) were investigated to reduce the turbulent skin friction drag of a low-speed airfoil. The induced jet characteristics of the two actuators in quiescent air were diagnosed with high-speed particle image velocimetry (PIV), and their drag reduction efficiencies were examined under different operating conditions in a wind tunnel. The results showed that the grid-type plasma actuator was capable of producing a wall-normal jet array (peak magnitude: 1.07 m/s) similar to that generated in a micro-blowing technique, while the super-dense array plasma actuator created a wavy wall-parallel jet (magnitude: 0.94 m/s) due to the discrete spanwise electrostatic forces. Under a comparable electrical power consumption level, the super-dense array plasma actuator array significantly outperformed the grid-type configuration, reducing the total airfoil friction drag by approximately 22% at a free-stream velocity of 20 m/s. The magnitude of drag reduction was proportional to the dimensionless jet velocity ratio ( r ), and a threshold r = 0.014 existed under which little impact on airfoil drag could be discerned.